2023
DOI: 10.1039/d3sc03548d
|View full text |Cite
|
Sign up to set email alerts
|

Main group metal-mediated strategies for C–H and C–F bond activation and functionalisation of fluoroarenes

Neil R. Judge,
Alessandra Logallo,
Eva Hevia

Abstract: This Perspective showcases recent advances on the use of specially designed main-group metal complexes to facilitate chemoselective C–H/C–F functionalisation of fluoroarenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 98 publications
0
5
0
Order By: Relevance
“…Hevia and coworkers have considerably extended the alkali–metal - ate chemistry 136–138 and very recently reported the dehydrometallation of fluoroarenes mediated by cobalt alkali–metal amides (Fig. 37).…”
Section: Heterobimetallic Systems Involving Main-group Metallic Elementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hevia and coworkers have considerably extended the alkali–metal - ate chemistry 136–138 and very recently reported the dehydrometallation of fluoroarenes mediated by cobalt alkali–metal amides (Fig. 37).…”
Section: Heterobimetallic Systems Involving Main-group Metallic Elementsmentioning
confidence: 99%
“…134,135 Regioselective functionalization of fluoroarenes can be challenging due to uncontrolled reactivity and unwanted side reactions such as benzyne formation or cascade processes (auto-metalation, multi-metalation). 138 Heterobimetallic amide bases combining an alkali metal with a divalent transition-metal center not only prevent these side reactions but also allow new reaction pathways towards thermally stable metalates under mild conditions. Unlike in many established C–H bond activation processes, the oxidation state of the 3d-transition metal remains unchanged throughout the reaction.…”
Section: Heterobimetallic Systems Involving Main-group Metallic Elementsmentioning
confidence: 99%
“…41 and Chirik, 64 and by Davies, Macgregor, and McMullin. 65 In addition, a perspective focusing on the activation and functionalization of C−H and C−F bonds in fluoroarenes by main group elements has recently been published by Hevia et al 66 In this section, we address the origins of selectivity between different positions in a particular fluorine-substituted benzene ring for activation by transition metals, for which there is rich experimental evidence. There is little (if any) experimental information about competition between different isomeric fluorobenzenes, e.g., between 1,2-C 6 F 2 H 4 , 1,3-C 6 F 2 H 4 , and 1,4-C 6 F 2 H 4 , although computational studies provide predictions.…”
Section: Reactivity Of the C−h Bonds Of (Poly)fluoroarenesmentioning
confidence: 99%
“…Motivated by the ability for nickel to functionalize challenging electrophiles, herein, we explore the stoichiometric and catalytic reactivity of low-valent [formally Ni(0)] nickelate Li 3 (TMEDA) 3 Ni­(CC–Ph) 3 toward aryl fluorides and polyfluoroarenes (Scheme b). While the C–F activation of polyfluorinated arenes is well established for many transition-metal and low-valent main-group complexes, the selective C–F functionalization of monofluorinated arenes is challenging due to the high bond dissociation energy (BDE) of the C­(sp 2 )–F bond (125.6 kcal mol –1 for Ph–F vs 114 kcal mol –1 for C 6 F 6 and 65.1 kcal mol –1 for Ph–I) . The C–F activation of monofluorinated arenes provides opportunities for orthogonal cross-coupling strategies or the late-stage functionalization of substituted arenes, , and numerous stoichiometric, catalytic, and mechanistic studies have been reported to date using nickel complexes. …”
Section: Introductionmentioning
confidence: 99%